2010
DOI: 10.1097/aln.0b013e3181d3e0c2
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Activates Cell Cycle Signaling and Apoptosis in the Neonatal Rat Brain

Abstract: These findings support a model in which ketamine induces aberrant cell cycle reentry, leading to apoptotic cell death in the developing rat brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 26 publications
5
57
1
Order By: Relevance
“…In studies with seven-day-old rats where loss of pyramidal neurons was induced, levels of caspase 3 were increased in the hippocampus upon administration of sevofl urane, propofol and ketamine (17,(21)(22)(23)(24). In our study, cortex caspase 3 levels were found to be signifi cantly higher in the sevofl urane group compared to the control group.…”
Section: G D Hsupporting
confidence: 55%
“…In studies with seven-day-old rats where loss of pyramidal neurons was induced, levels of caspase 3 were increased in the hippocampus upon administration of sevofl urane, propofol and ketamine (17,(21)(22)(23)(24). In our study, cortex caspase 3 levels were found to be signifi cantly higher in the sevofl urane group compared to the control group.…”
Section: G D Hsupporting
confidence: 55%
“…Changes in the neuronal cytoskeleton have also been observed, possibly via the p75 NTR receptor and subsequent RhoA activation [28]. Altered neurogenesis and abnormal re-entry into the cell cycle has also been observed [29,30]. Lastly, anesthetics have been shown to impair mitochondrial function [31].…”
Section: Effects Other Than Apoptosismentioning
confidence: 97%
“…Ketamine is an NMDA receptor antagonist that is widely used in pediatric anesthesia, and sub-anesthetic doses of ketamine are frequently used for perioperative sedation, analgesia, and other diagnostic procedures in pediatric patients. It is also known that ketamine can cause neuronal apoptosis in the developing mammalian brain [2,3,4,5,6,7,8,13,14] and, consequently, long-term defects in learning and memory [3,46]. When immature neurons are exposed to blockers of NMDA receptors, these cells activate a compensatory mechanism following withdrawal that causes increased expression of NMDA receptors, leading to increased sensitivity to extracellular glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…The first preclinical study investigating neurotoxicity in the early stages of central nervous system (CNS) development following exposure to NMDA receptor antagonists was reported in 1999 [1]. Since then, a series of animal experiments have shown that repeated administration of ketamine can trigger neurodegeneration in the developing brain, leading to long-term defects in cognitive behavior [2,3,4,5,6,7,8,9]. The mechanism leading from ketamine uptake to neuronal cell death remains unclear.…”
Section: Introductionmentioning
confidence: 99%